2020
DOI: 10.51791/njap.v44i5.1335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diets containing raw and processed pigeon pea seed meal on external and internal egg quality characteristics of laying quails (Coturnix coturnix japonica ) Ke

Abstract: Three hundred and sixty, sixweek old Japanese quail hens (Coturnix coturnix japonica)were used to evaluate the effect of processed pigeon pea (Cajanus cajan) seed meal (PPSM) on egg quality characteristics of laying birds. The processingmethodswere soaking (24, 48 and 72 hours), fermentation (72 hours), boiling (60minutes) and roasting (30minutes). The birds were divided into eight groups of 45 per treatment each replicated three times with 15 birds per replicate in a completely randomized design. The birds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…Albumen length, diameter, weight and eggshell weight were all significantly higher in birds fed 5% PLM which implies that when PLM is fed at an optimum level it does have a positive effect on these parameters as observed in this study. This finding disagrees with the report of Akintunde et al 33 , who reported no significant differences in internal egg quality traits of quails fed differently processed pigeon pea meal. The variation could be attributed to differences in diet composition.…”
Section: Discussioncontrasting
confidence: 99%
“…Albumen length, diameter, weight and eggshell weight were all significantly higher in birds fed 5% PLM which implies that when PLM is fed at an optimum level it does have a positive effect on these parameters as observed in this study. This finding disagrees with the report of Akintunde et al 33 , who reported no significant differences in internal egg quality traits of quails fed differently processed pigeon pea meal. The variation could be attributed to differences in diet composition.…”
Section: Discussioncontrasting
confidence: 99%